PELATIHAN TEKNIK SAMPLING DAN ANALISIS DATA STATISTIK PADA PENELITIAN KUANTITATIF - Elok Fitriani Rafikasari; Risdiana Chandra Dhewy; Moch. Dicky Riza (STKIP PGRI Sidoarjo, 2023)
This training activity aims to improve participants' abilities in collecting, processing and analyzing research-related data in quantitative form. The activity was attended by students from the Sharia Economic Law Study Program at UIN Sayyid Ali Rahmatullah Tulungagung. The material provided during training concerns sampling techniques and various test statistics in data analysis for quantitative research. The stages in this training activity include presentation of material by resource persons, questions and answers and interactive discussions with participants, operating SPSS software. The response from the training participants was very good as shown by the participants' interest when asking questions or discussing during the activity so that this activity could be carried out according to expectations.